Research, intervention and education for conservation and restoration of the Archaeological Park of Cochasqui (Ecuador) - Carrascosa Moliner, Begoña (2018)
Due to the increasing interest in the conservation of the Archaeological Park of Cochasqui, and thanks to the project: Cultural Development and Cooperation for the Enhancement value of the pre-Incan Pyramids of Cochasquí, Ecuador, has developed several conservation and restoration actions for the recovery of two pre-Inca ceramic structures on pyramid number 13 of the archaeological complex. With the purpose of recovery these demonstrations, that were found in an alarming state of damage, this project developed three specific lines of action: the research on replacement materials in laboratory, in situ restoration, and social appropriation of the Cochasquí heritage, so as to guarantee its safeguard and protection. All thanks to the grant from the Spanish Ministry of Foreign Affairs through the Spanish Agency of International Cooperation for Development AECID, and the collaboration of Polytechnical University of Valencia, Spain (UPV) and Pichincha’s Decentralized Provincial Government, Ecuador.